2017
DOI: 10.1123/jsr.2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Movement Screen in the Prediction of Injury in Adolescent Cricket Pace Bowlers: An Observational Study

Abstract: Preseason observed total FMS score is a poor predictor of in-season injury among adolescent pace bowlers. Further research should be conducted to determine if a specific FMS test will be a more valid predictor of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Considering the results of the studies with low risk of bias (Table 3), it is verified that FMS has a low sensitivity 20,22,40 , a good specificity 20,33 , and AUC values slightly above chance 20,22 . Three out of the four studies with low risk of bias used samples composed of soldiers 20,33,40 . These studies showed a higher score in the "selection" domain.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Considering the results of the studies with low risk of bias (Table 3), it is verified that FMS has a low sensitivity 20,22,40 , a good specificity 20,33 , and AUC values slightly above chance 20,22 . Three out of the four studies with low risk of bias used samples composed of soldiers 20,33,40 . These studies showed a higher score in the "selection" domain.…”
Section: Discussionmentioning
confidence: 84%
“…OR values also ranged from 0.53 to 11.67, which corresponds, according to the literature, to absent and large effect sizes, respectively 41 . Only seven studies calculated the RR 20,27,34,35,40,42,43 , whose results were RR=1.86 (overuse injuries) 22 , RR=1.49 (traumatic injuries) 22 ; and RR=-0.5 40 to 2.73 39 (any injury). Thus, a low score in FMS™ is associated with higher injury risk, although this result is limited by the number of studies that calculate the RR and the high risk of bias in two of those studies 27,34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have therefore proposed that a history of previous injuries is a risk factor for future damage (4). A large body of literature has been dedicated to the FMS test as an effective tool for predicting injuries in athletes before participating in competitions in different sports fields (5,6).…”
Section: Introductionmentioning
confidence: 99%